The Scholarship of Massimo Bernabò: an appreciation - Peers, Glenn (Orientalia christiana periodica, 2024)
This essay provides an overview of some major contributions that Massimo Bernabò has made to the discipline of Byzantine art history over the course of his long career. It seeks to identify longterm concerns (manuscript illustration survivals and reconstructions, historiography, Syriac culture) and significant qualities that make his body of work necessary reading.